Skin reactions after use of ketoprofen and sun exposure – report of two cases - Lis-Święty, Anna; Bergler-Czop, Beata; Trzmiel, Dorota (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Drug photosensitivity constitutes a large group of photodermatoses. The evoking drugs include: diuretics, antibiotics, cardiovascular and non-steroidal anti-inflammatory preparations. Photoallergy is a form of photosensitivity that is immunologically mediated and is much rarer than phototoxicity. Both topically applied and systemically administered substances can produce photoallergic reactions. The onset of skin lesions is usually delayed for 24 hours or even for several days, and recovery is often slower than from a phototoxic reaction. The reaction sometimes persists for some time after the offending product has been discontinued. Photoallergic reaction presents as a pruritic eczematous eruption with erythema, papules and vesicles, weeping, oozing and crusting, and in later stages scaling and lichenification. Objective. Presentation of two cases of skin reactions related to sun exposure after use of ketoprofen. Case reports. Case 1. Patient with drug eruption in sun exposed areas associated with systemic use of ketoprofen. Case 2. Patient with contact dermatitis due to topical application of ketoprofen and sun exposure. In both cases skin biopsy was consistent with eczema. Conclusions. The clinical picture in the presented cases may indicate a photoallergic reaction after use of ketoprofen. The use of this drug in a period of pronounced sun exposure may be associated with the risk of severe skin reactions.